Danish Validation of a Retronasal Olfactory Powder Test and Development of a Novel Quick Retronasal Olfactory Test - Niklassen, Andreas Steenholt; Sakthivel, Sukanya; Fjaeldstad, Alexander Wieck; Ovesen, Therese (International Archives of Otorhinolaryngology, 2022)
Introduction Quality of life is closely linked to retronasal olfactory function. Familiarity with odors vary, so tests need validation. Testing can be time-consuming, so a quick test and a thorough test are needed for clinical and research settings.Objectives The objectives of this study were to validate the original retronasal powder olfactory test in a Danish population and to develop a novel quick retronasal test for easy application.Methods Ninety-seven participants were included in the study, 59 healthy controls and 38 patients with olfactory impairment. The retronasal test was modified by substituting unfamiliar odors and descriptors and validated with a criterion of correct identification rate of 50% in the original test and 90% in the quick test. Items with over 90% correct identification rate in the modified original test were included in the quick test, resulting in a 10-item test.Results The modified retronasal olfactory test achieved good test characteristics, with a 10th percentile cut-off value of 13: sensitivity was 88.9%, specificity 83.0%, positive predictive value 78%, negative predictive value 91.7%, and the receiver operating characteristics area under the curve (ROC-AUC) was 0.86. The quick test achieved acceptable test characteristics, with a 10th percentile cut-off value of 8.2: sensitivity was 72.2%, specificity 90.6%, positive predictive value 83.9%, negative predictive value was 82.8%, and ROC-AUC 0.81.Conclusion Validation of both tests demonstrated satisfactory accuracy. We recommend the quick test for screening purposes, and the modified original version for a thorough evaluation. The tests are easily implemented as they are easy to understand and very affordable.
Keywords: smell; olfaction disorders; anosmia; diagnosis; validation study